Optimisation of Injection Moulding Process Parameters - Guna Rao, Kishyen Raao; Nur Qurratul Ain, Adanan; Anis Izzati, Md Yusoff; Faiz, Mohd Turan; Norazlianie, Sazali (Semarak Ilmu Publishing, 2024)
It is crucial to develop new techniques for recycling or reusing plastic components given their widespread manufacture and the fact that natural processes cannot break them down. Injection moulding, among the most common plastic processing processes, allows recycled materials to be swapped for virgin material during the manufacturing process of plastic objects. Furthermore, the primary challenge that significantly limits the application of recycled plastic is the loss of the mechanical qualities of recycled plastic components. The presence of variability in the processing parameters is one of the most important contributing elements. During the production process, it is of the utmost importance to successfully regulate all influencing processing parameters by utilizing an appropriate optimisation strategy. Considering this, the primary purpose of this research is to study the effect that the best parameters used for injection moulding have on the mechanical qualities of recycled plastic components.